UPPER JURASSIC (TITHONIAN) AMMONITES FROM THE SPITI SHALES IN WESTERN ZANSKAR (NW HIMALAYAS) (Rivista italiana di Paleontologia e Stratigrafia, 1990)
A description is given of the ammonites collected during the Italian expedition to the Zanskar region of the NW Himalayas in 1984. The paleontological analysis is made in the context of a depositional and ecological model proposed for Spi ti Shales facies. The genera Uhligites, "Virgatosphinctes ", Aulacosphinctes and Parapallasiceras are identified. An upper to uppermost Lower Tithonian age is assigned for the highest levels of the Spiti Shales Fm. in the sector examined, although it may be possible that the extreme base of the Upper Tithonian is also represented.